Relationship Between Knowledge and Attitude of the Community with Blood Clam Processing Behavior in Rusun UPRS Blok G Muara Angke Jakarta in 2025 - Amy Ravita Sari; Nanny Harmani (PROMOTOR, 2026)
Blood clams are a seafood widely consumed by coastal communities, including in Muara Angke, Jakarta. However, blood clams are susceptible to microplastic contamination due to marine pollution. Consumption of seafood contaminated with microplastics can cause health impacts, such as organ and hormonal disorders. This study aims to determine the relationship between community knowledge and attitudes with blood clam processing behavior in Rusun UPRS Blok G Muara Angke. This study used a quantitative approach with a cross-sectional design. The sample consisted of 117 respondents from RT 10, RT 11, and RT 12, selected proportionally. The instrument was a questionnaire that had been tested for validity and reliability. The results showed that 76.1% of respondents had high knowledge, 56.4% had a positive attitude, and 64.1% showed good consumption behavior. The chi-square test showed no significant relationship between knowledge and consumption behavior (p = 0.074), but there was a significant relationship between attitude and consumption behavior (p = 0.014). These results indicate that attitude has a greater influence on safe processing behavior than knowledge. Further education is needed for the community regarding the dangers of microplastics and safe seafood processing methods.